2015
DOI: 10.1096/fasebj.29.1_supplement.898.18
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Links – Building Capacity for Sustainable Lives in Ghana

Abstract: The Upper Manya Krobo District is an impoverished, underserved rural area in the Eastern region of Ghana. To improve the quality of services offered by district institutions and ameliorate the health and economic well‐being of vulnerable populations, we initiated a multi‐sector, 5‐y, district‐wide project “Nutrition Links”. An annual survey of all 1081 households with young infants provides information on health, nutrition, agriculture, and economic activities; this information is being used to develop project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A meta-analysis involving 29,160 Ghanaian children across sixteen studies reported 8.6% obesity and 10.7% overweight [7]. There exists a signi cant number of studies that quanti es the burden of obesity in Ghana with a special focus on the general adult population [8][9][10][11][12][13], women [14][15][16][17][18][19][20], school-aged children [21][22][23], adolescents [24][25][26], healthcare workers [27][28][29][30][31], civil servants [32][33][34][35][36][37] and commercial workers [38]. However, knowledge and data about the experiences of being overweight and obese among young Ghanaian adults are inadequate.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis involving 29,160 Ghanaian children across sixteen studies reported 8.6% obesity and 10.7% overweight [7]. There exists a signi cant number of studies that quanti es the burden of obesity in Ghana with a special focus on the general adult population [8][9][10][11][12][13], women [14][15][16][17][18][19][20], school-aged children [21][22][23], adolescents [24][25][26], healthcare workers [27][28][29][30][31], civil servants [32][33][34][35][36][37] and commercial workers [38]. However, knowledge and data about the experiences of being overweight and obese among young Ghanaian adults are inadequate.…”
Section: Introductionmentioning
confidence: 99%